TACTICS OF ALGORITHMIC LITERACY: HOW YOUNG PEOPLE UNDERSTAND AND NEGOTIATE ALGORITHMIC NEWS SELECTION - Swart, Joelle (AoIR Selected Papers of Internet Research, 2020)
With the growing centrality of the smartphone in everyday life, the news and public information that young people consume is increasingly subject to algorithmic curation. From the apps and websites of legacy news media to news aggregators and social media, more and more spaces through which young people access news are personalized. Yet, while numerous studies explore algorithms’ influence on citizens’ everyday life, few of these have considered how users themselves perceive and deal with news personalization. This paper considers how young news users experience the algorithmic selection of the news they receive via their smartphones, and how and under what circumstances they aim to negotiate these decisions. Combining walk-through methods with in-depth interviews, it explores young people’s perceptions of algorithms affect their practices on personalized news media and how they aim to intervene in news personalization. The paper finds a variety of tactics through which audiences intervene in algorithmic news selection, arguing that these can be seen as expressions of algorithmic literacy. These practices, however, are far from self-evident: overall, even amongst frequent users of personalized media, algorithmic awareness and knowledge are low. Moreover, such literacy varies considerably between platform contexts. This is problematic, as these deficiencies prevent young people from assessing the completeness, accuracy and balance of the news they are exposed to. Thus, the study stresses a need for media educators to pay more attention to how algorithmic curation shapes the news that users encounter, to further empower young people to navigate an increasingly personalized media landscape.